Faith-Based Leadership Integration: Applying Prophetic Values in Transformational and Servant Leadership for SME Entrepreneurs - Dikriyah; Muhammad Hariyadi; Suprihatin (jfpublisher, 2026)
Leadership represents a critical determinant of entrepreneurial success and organizational sustainability, particularly within small and medium enterprises where ethical guidance directly influences stakeholder outcomes. This study analyzes the integration of Prophet Muhammad's leadership values within transformational and servant leadership models through systematic thematic Quranic exegesis. Employing qualitative descriptive methodology with tafsir maudhu'i approach, the research examines four key Quranic verses (Al-Imran 3:159, Al-Anbiya 21:107, Al-Furqan 25:63, and Al-Ma'idah 5:8) that articulate principles of consultative decision-making, visionary inspiration, humble conduct, and equitable justice. Findings reveal that prophetic leadership encompasses both transformational dimensions (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration) and servant leadership characteristics (humility, empowerment, ethical behavior, and stewardship) within a unified theological framework. The analysis demonstrates that Quranic leadership principles challenge the artificial dichotomy between transformational vision-setting and servant stakeholder orientation prevalent in Western management scholarship, instead presenting an integrated paradigm termed